Rapid sintering process and mechanical properties of binderless ultra fine tungsten carbide - Kim, Hwan-Cheol; Yoon, Jin-Kook; Doh, Jung-Mann; Ko, In-Yong; Shon, In-Jin (ELSEVIER SCIENCE SA, 2006)
The rapid sintering of ultra fine WC hard materials in a short time was investigated with a focus on the manufacturing potential of high-frequency induction heating sintering process. The advantage of this process is that it allows very quick densification to near theoretical density and prohibition of grain growth in ultra fine materials. A dense pure WC hard material with a relative density of up to 98.5% was produced with simultaneous application of 60 MPa pressure and induced current of output of total power capacity (15 kW) within 2 min. A larger output of total power capacity caused a higher rate of temperature increase and therefore a higher densification rate of the WC powder. The finer the initial WC powder size the higher the density and the better mechanical properties. The fracture toughness and hardness values obtained were 7.1 MPa m(1/2) and 2854 kg/mm(2), respectively, under 60 MPa pressure and 90% output of total power capacity using 0.4 mu m WC powder. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: INDUCTION HEATED COMBUSTION; CO HARD MATERIALS; CEMENTED CARBIDE; SURFACE-AREA; WC; MICROSTRUCTURE; CONSOLIDATION; SIZE; MOLYBDENUM; TOUGHNESS